Development, drying characteristics, and environmental analysis of a PV operated automatic solar dryer for drying date - Elwakeel, Abdallah Elshawadfy; El-Mesery, Hany S.; Elbeltagi, Ahmed; Salem, Ali; Sabry, Ayman; Saleh, Dalia I.; Moustapha, Moustapha Eid; Abu-Taha, Hadeer L.; Elkot, Wael F. (Frontiers in Sustainable Food Systems, 2025)
The current study aims to develop and conduct a techno-environmental evaluation of a new sustainable forced convection solar dryer (SFCSD). Where the developed SFCSD was integrated with a unique electronic circuit that enables it to operate in two different modes: 1. forced air circulation (active mode) and 2. natural air circulation (passive mode), based on the air temperature (AT) inside the drying room and the ambient light intensity (Li). Furthermore, the SFCSD is equipped with an early warning system (SOS) that can send a warning message (SMS) to the operator in case of system failure. The Aswan region of Egypt uses the developed SFCSD to dry the most famous five date fruit varieties (Shamia, Bartamuda, Sakkoti, Malkabii, and Gondaila). The speed sensor of air suction fan, Li sensor, relative humidity (RH) sensor and AT sensor were calibrated against standard devices before used. The results showed a strong correlation between the measured and reference values. Despite the slight underestimation of the values, the sensors’ response remains consistent and predictable. The R2 values for the speed sensor, the Li sensor, the AT sensor, and the RH sensor were, in that order, 0.9904, 0.987, and 0.9863. The average daily solar radiation, ambient AT, and RH during field tests were 494.78 W/m2, 29.46°C, and 23.68%, respectively. The initial moisture content (MC) of the different date fruit (DF) varieties used in the current study ranged between 10.32 and 12.56%, and the DF samples reached equilibrium MC at 9 days. The effective moisture diffusivity (EMD) ranged between 3.5569 × 10−7 m2/s and 3.9489 × 10−7 m2/s. The maximum efficiency of the photovoltaic (PV) system and the solar collector was 25.28 and 69.52%, respectively. The analysis of environmental impact revealed that the energy payback time (EPP) for the developed SFCSD is 7.15 years, which represented only 23.83% of the system’s lifetime. The developed SFCSD has a CO2 mitigation value of 93.2 tons and earned carbon credit (ECC) valued of 6757.02 USD throughout its estimated lifetime of 30 years. The environmental impact analysis demonstrates that the developed SFCSD is an appropriate alternative for preserving agricultural products while maintaining environmental sustainability.